Dawne piśmiennictwo religijne - inspirujące i nadal odkrywane dziedzictwo - Trościński, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The present issue of our journal is devoted to Old Polish and Enlightenment religious literature as well as themes and conventions of religious literature. The articles show a rich tradition of such works. The broad scope of topics demonstrates diverse literary research. The articles are devoted to defining such terms as "religious literature" and "religious poet", as well as to translations and biblical inspirations, prayers and meditations, monastic authors and their works, hymnals, sermons and the rhetoric, the matter of faith and reason, and a Sarmatian religion. The present issue of "Tematy i Konteksty" ("Themes and Contexts") also includes the papers devoted to interpretation of 19th century literature, reviews, reports and announcements. The authors of studies are scholars from a range of academic institutions in Poland.
Old-Polish and 18th Century Religious Literature as an Inspiring and still Undiscovered Heritage
Keywords: literatura staropolska; oświecenie; literatura religijna; "Tematy i Konteksty"; Old-Polish literature; Enlightenment; religious literature; "Themes and Contexts"